PENERAPAN MODEL INTERAKSI SOSIAL DALAM MENINGKATKAN KETERAMPILAN KOMUNIKASI DAN KERJA SAMA SISWA SEKOLAH DASAR - Sri Muliani (CV. ADIBA AISHA AMIRA, 2026)
This study aims to describe the implementation of the social interaction model in improving communication and collaboration skills of elementary school students. The social interaction model is a learning approach that emphasizes students’ active involvement through interaction, discussion, and group work. The implementation of this model is carried out through group formation, collaborative tasks, discussions, and presentations of group work. The results show that the social interaction model has a positive impact on students, particularly in improving their confidence in speaking, ability to express ideas, and teamwork skills. In addition, this model also fosters social attitudes such as respect, tolerance, and responsibility. Therefore, the application of the social interaction model can create an active, enjoyable, and meaningful learning environment for elementary school students.